HADIS SEBAGAI SUMBER ETIKA SOSIAL DALAM PENDIDIKAN ISLAM KONTEMPORER - Azmi Yudha Zulfikar (lembaga Sepercenter, 2024)
The hadiths of the Prophet Muhammad SAW are the main source of Islamic teachings after the Qur'an, containing many dimensions, including social ethics. In the context of contemporary Islamic education, social ethical values derived from the hadiths are urgent to be contextualised in the character building of students. This article aims to explore the contribution of the Hadith as a foundation for fostering social ethics in the modern Islamic education system, as well as addressing the challenges of social values in an increasingly complex society. Through a qualitative approach using literature review, this article highlights that values such as honesty, justice, social responsibility, empathy, and solidarity contained in the hadith can serve as pillars of Islamic character education that are relevant and applicable in the era of globalisation